President's Message - Pimentel, Justinian Aquilino IV Cyril Ll (Philippine Journal of Orthopaedics, 2025)
Mabuhay! I am proud to present the third issue of the Philippine Journal of Orthopaedics for 2025. This edition showcases studies that reflect the strength of orthopaedic practice in the Philippines—from innovations in trauma and tumor care to insights that improve patient outcomes, even in a resource-limited setting. I congratulate and thank the authors and the entire editorial team for their tireless scholarly work and for sharing their knowledge, expertise, and experiences with the orthopedic community. May this issue inspire more of us to contribute to building a stronger and more relevant local orthopedic pool of knowledge. Mabuhay ang Philippine Journal of Orthopaedics at ang Philippine Orthopaedic Association!